Pengaruh Risiko Sistematik Dan Rasio Pasar Terhadap Return Saham Syariah Pada Perusahaan Yang Terdaftar Dalam Indeks Saham Syariah Indonesia - Thayyibah, Syahriannisa; Silalahi, Alisraja Dison (UNIVERSITAS DHARMAWANGSA, 2023)
This research aims to determine the effect of systematic risk and market ratios on sharia stock returns in companies listed in the Indonesian sharia stock index for 2020-2022. The independent variables in this research are systematic risk and market ratios and the dependent variable in this research is stock returns. The research sample is companies listed in the 2020-2022 Indonesian Sharia Stock Index. The sample was selected using a purposive sampling technique to obtain 12 companies listed in the sharia stock index. This research uses multiple linear regression analysis research methods. The research results show that systematic risk and market risk have a positive effect on sharia stock returns simultaneously.Keywords: systematic risk, market ratio, Islamic stock returns.